222k views
5 votes
Simplify the expression. Write the answer with positive exponents only. Assume the variable represents a nonzero real number.

Simplify the expression. Write the answer with positive exponents only. Assume the-example-1

1 Answer

3 votes

Answer:


(1)/(w^(29))

Explanation:

The given expression is
(w^(-7)(w^(-9))^2)/(w^4).

Since,
w^(-7)=(1)/(w^7)

And
w^(9)=(1)/(w^9)

Expression will become,


(w^(-7)(w^(-9))^2)/(w^4)=((1)/(w^7)((1)/(w^9))^2)/(w^4)


=((1)/(w^7* w^(18)))/(w^4)


=((1)/(w^((7+18))))/(w^4)


=(1)/(w^(25))* (1)/(w^4)


=(1)/(w^(25)* w^4)


=(1)/(w^(29))

Therefore, Simplified form of the given expression will be
(1)/(w^(29)).

User Termi
by
5.5k points